Barriers to Enhancing Disaster Risk Reduction and Community Resilience: Evidence from the L’Aquila Disaster - Imperiale, Angelo Jonas (2020)
Building sustainable and resilient societies is a multidimensional challenge that affects achievement of the 2030 Agenda for Sustainable Development. In crises and disasters, civil protection authorities typically use emergency powers and a command-and-control approach to manage resources and to design and implement disaster management interventions. They centralise knowledge, technologies and responsibilities for prevention, mitigation and monitoring, while stifling the capacities of local communities to reduce disaster risks and impacts. The mechanism they enact leads to a poor understanding of the capacities of local people to learn and transform, and of how community wellbeing, vulnerabilities, and resilience influence disaster risks. The mechanism does not strengthen the role of local communities in disaster risk reduction. Instead, it facilitates disaster capitalism at all levels of society. Drawing on the disaster risk reduction and resilience paradigm and on our analysis of the disaster management interventions conducted before and after the 6 April 2009 earthquake in L’Aquila, Italy, we discuss the main constraints to implementing the four Priority Areas in the Sendai Framework for Disaster Risk Reduction: (1) Understanding risk in its multiple dimensions; (2) strengthening disaster risk governance; (3) investing in disaster risk reduction for resilience; and (4) enhancing preparedness and build back better in response, recovery and reconstruction. We discuss how top-down, emergency-centred civil protection approaches create second disasters, and fail in all four priorities. We suggest that shifts in paradigm and investment are required in disaster management and development practice from centralised civil protection systems to decentralised, socially sustainable community empowerment systems.